Nonlinear photoluminescence imaging applied to femtosecond laser manufacturing of fiber Bragg gratings - Hnatovsky, C; Grobnic, D; Mihailov, S. J (Optics express, 2017)
Nonlinear photoluminescence imaging is used to visualize the intensity distribution of femtosecond laser pulses inside the optical fiber during Bragg grating inscription based on side illumination through a phase mask. This technique, which results in direct imaging of the inscription laser field inside the optical fiber, facilitates i) the characterization of the laser focus in the vicinity of the fiber core and ii) the optimization of the fiber alignment with respect to the laser focus while using pulses with energies several times lower than those used during the actual inscription process. The applicability of this imaging technique is demonstrated for Bragg grating inscription in different optical fibers, including direct inscription through the fiber coating.